Effect of Nitrogen Fertilization on Some Chemical Constituents of Kernels of Three Varieties of Wheat Grown in Libya - SAWHNEY, JAGDEV S.; STOYANOV, VLADIMIR (The Libyan Journal of Agriculture, 2023)
Crude protein per hectare in dry matter and organic matter of grain was determined for Sedi Mesri 1, Florence aurora and Chilli varieties of wheat. Crude protein increased with the increase of nitrogen fertilization. The grain yield and crude protein could be simultaneously increased by nitrogen fertilization. Percent ash in different treatments was erratic. The percentage of crude protein in Sedi Mesri 1, a high yielding short stemmed variety, could not be increased to the level of other varieties even by the highest nitrogen treatment. The grain yield was more important than percent crude protein in crude protein production per hectare.